Christopher Isherwood encyclopedia - Izzo, David Garrett (McFarland & Co., 2005)
"Major entries appear on Isherwood's most influential friends, including W.H. Auden, Aldous Huxley and Stephen Spender. All of the monumental 'roles' Isherwood exemplified during his life-writer, rebel, gay-activist hero, and proud exponent of the Eastern philosophy known as Vedanta-are fully covered"--Provided by publisher